Pressure vessel design the direct route - Zeman, Josef L.
Explores an approach to pressure vessel design, included in the (harmonized) standard EN 13445 (for unfired pressure vessels) and based on linear as well as non-linear Finite Element analyses. Examples are included to familiarize readers with this approach, to highlight problems and solutions, advantages and disadvantages.